Effect of moisture condition on cement masonry blocks with different ﬁne aggregates: river sand, lateritic soil and manufactured sand - Sathiparan, N.; Anburuvel, A.; Maduwanthi, K.A.P.N.; Dasanayake, S.R.A.C.B. (Springer, 2022)
With the escalating infrastructure developments in recent years, the demand for river sand has signiﬁcantly increased due to its importance as a raw material in the construction industry. River sand exca- vation from the river bed, on the other hand, is restricted due to environmental concerns. It has caused an insufﬁcient source of river sand to meet the present demand and thus forced the researchers to ﬁnd alternative materials for river sand. Even though agricultural wastes and industrial wastes have been considered as potential alternatives in the past, researchers recommend lateritic soil and manufactured sand as they both comply with requirements for mechanical properties. Published literature shows that masonry blocks with M-sand and lateritic soil satisfy the minimum strength requirement. However, studies on the durability of these blocks, especially under extreme weather, are rare to ﬁnd in the existing literature. The present study focuses on the moisture effects on cement masonry blocks cast with three types of ﬁne aggregates; river sand, lateritic soil and manufactured sand. Moisture characteristics and the moisture effect on the mechanical performance of cement- sand blocks, cement stabilized earth blocks and cement-manufactured sand blocks were thoroughly investigated in this study. Results reveal that mechanical characteristics of cement stabilized earth block is adversely affected by moisture whereas, cement-manufactured sand blocks show better mechanical characteristics than cement- sand blocks under moisture conditions.
Keywords: Masonry; Moisture; M-sand; River sand; Lateritic soil